Synthesis and characterization of novel pH sensitive PAAM-PMAA-CMC hydrogels and their applications in the controlled release of fertilizer - Aouada, Fauze A. [UNESP]; Bortolin, Adriel; De Moura, Márcia R.; Longo, Elson [UNESP]; Mattoso, Luiz H.C. [UNESP] (My University, 2012)
Recently, the applications of hydrogels as a carrier vehicle for the controlled release of fertilizers in the agricultural field have been extensively proposed due to the unique properties of these materials, such as their biodegradability, low-toxicity, high water uptake and reversible properties. The major benefit of these systems when applied in the agricultural setting is the gradual release of a loading, which maximizes that loading's concentration in the soil over a long time period. As a direct consequence, the number and frequency of the fertilizer applications to the soil are reduced. This diminishes the cost of agricultural production as well as the risks of human contamination and environmental pollution. This chapter is intended to describe the preparation of novel hydrogels composed of poly(acrylamide) (PAAm) / poly(methacrylic acid) (PMAA) / carboxymethyl cellulose (CMC) synthesized by a free-radical polymerization reaction catalyzed by temperature for applications in the controlled release of fertilizers. Fourier transform infrared (FTIR) spectroscopy confirmed the formation of the PAAm-PMAA-CMC hydrogels. The hydrophilic properties, determined by the degree of swelling, were dependent on the pH of the external swelling medium, indicating that this hydrogel is pH sensitive. The pKa value of the hydrogel estimated from the sigmoid-curve was approximately 4.0. It was also possible to control the amount and rate of water absorbed by controlling the monomer and polysaccharide compositions. The amount of water absorbed is directly related to the network rigidity. The Freundlich model performed better than the Langmuir model in describing the adsorption isotherm of the PAAm-PMAA-CMC/(NH4)2SO4 fertilizer system. The KF and 1/n Freundlich constants were 3.242 L g-1 and 0.4143, respectively. Thermodynamic investigations proved that the adsorption of the fertilizer in the hydrogels is spontaneous. An investigation of the cumulative desorption confirmed that these hydrogels have potential applications in the agricultural field. © 2012 Nova Science Publishers, Inc. All rights reserved.